COMPARATIVE ANALYSIS OF THE WORKS OF TAKIUDDIN MUHAMMAD AVHADIY “ARAFOT-UL-OSHIQIN” AND MUTRIBIY SAMARKANDIY “TAZKIRAT-USH-SHUARO” (Scientific journal of the Fergana State University, 2023)
The article analyzes the work of Mutribi Samarkandi “Tazkirat-ush-shuaro”, which was written at the same time and at the same time on the same topic as the work of Takiuddin Muhammadi Avhadi “Arafot-ul-oshikin”.  The following version compares two anthologies that provide information on poets of the 16 th century who come to the conclusion that either Avkhadi did not see Mutribi's work “Tazkirat-ush-shuaro” or was not familiar with his information, especially about this in the work nothing is said. According to our observations, some facts say that there was an influence of the anthology of Mutribi on “Arafat-ul-oshikin”. The importance is also that in two anthologies, information about the life of poets is similar to each other. The article also narrates that to compare the two anthologies, the thoughts of poets such as Doii Andijani, Mavlo Hayeti, Anisi Iroki and others are given.In the final part of the article, laudatory information of the work “Arofot-ul-oshikin” is set forth, and in the work “Tazkirat-ush-shuaro” the information is significant with the correct narration and accuracy.  In some cases, the work “Arafot-ul-oshikin” replenished with data, it becomes clear that “Tazkirat-ush-shuaro” has greater significance.